Qualities of POME in different mills and their management practices: a case study in Perak / Sharasafarin Sapie @ Shafie - Sapie @ Shafie, Sharasafarin (Faculty of Plantation and Agrotechnology, 2018)
Palm of mill effluent or generally known as POME is the wastewater from palm oil mill. The purpose of this study was to determine the characteristics of Palm Oil Mill Effluent (POME) in different palm oil mills from different regions in Perak. The objective of the study was to determine the best management practices applied by palm oil mills in order to produce treated POME that follows the required parameter by Malaysian Department of the Environment (DOE). Data are collected from 19 palm oils mills and were analyzed according to the level of Biochemical Oxygen Demand (BOD), oil and grease, suspended solids, ammonical nitrogen, total nitrogen, temperature and its pH. From the study, there are some of the palm oil mills produce treated effluent that follows the parameter set by DOE while some did not and the best characteristics of treated effluent produced is by palm oil mils Batang Padang Region I. Through the study, it shows that the most important practice that should be applied by palm oil mills is by making sure the availability of bacteria in their pond as it will affects POME characteristics. Apart from that, the other practice that should be applied by palm oil mills is frequently submission of the result for treated effluent as applied by palm oil mill Hilir Perak Region I. This is a good practice as it may help them to analyze the reading for POME that they produced. The best application of the treated effluent is for biofertilizer as being applied by palm oil mill Hilir Perak Region III. Recommendations on what can be done by palm oil mills rather than discharge treated effluent into the watercourse are explained in this study. The recommendations include bio fertilizer, biogas and bio plastics.